Habitual Breakfast Consumption and Phyical Fitness Among Senior High School Student, Central Kalimantan - Uswatun Hasanah Purnama Sari; Zuly Daima Ulfa; Andi Tenri Abeng; Bayu Setya Yuda (Insights in Public Health Journal, 2023)
Background: Physical fitness is a person's ability to carry out daily activities without experiencing significant fatigue and still have energy reserves for other activities. In Indonesia, 40% of children skip breakfast. Skipping breakfast can affect the decrease in physical activity. This lack of physical activity has an impact on decreasing physical fitness, so that a person will be more easily tired and less optimal in carrying out daily activities. Methods: This study discusses the relationship of breakfast habits to physical fitness in students of SMA Negeri 1 Pangkalan Banteng, this research method is quantitative descriptive with a cross sectional approach, the sample amounted to 69 people taken using simple random sampling. Results: The results of the study used the chi square test and found that there was a relationship between breakfast habits on the physical fitness of students of SMA Negeri 1 Pangkalan Banteng (p = 0.035 < 0.05) Conclusions: Breakfast and physical freshness are both very important and support each other's benefits. Therefore, it is important to pay attention to the child's breakfast before activities